Astrology and power in the Roman Empire: the divination of Fate in the 'Anthologies' by Vettius Valens (2nd century A.D.) - Silva, Semíramis Corsi; Motta, Vinícius de Oliveira da (Romanitas - Revista de Estudos Grecolatinos, 2017)
The objective of this article is to analyze historically the work Anthologies, written in the middle of the second century AD by the astrologer Vettius Valens (120-188 AD), observing the role of stoic influence and, mainly, of a fatalistic notion of Fate (heimarmene) in the context of the Roman Principate. We will also analyze how Valens presents astrology in his discourse as a tool for anticipating the cosmic order through an unio mystica, qualifying, legitimizing and justifying both the knowledge of the mystical tradition he wishes to integrate and the profession of those who like him study and practice the prognostic art, which must be kept under some secrecy and control. Then, we will show how Vettius Valens claims power and superiority, a power marked by the ability of divination of the Fate.
Keywords: Astrology; Divination of the Fate; Power; Anthologies; Vettius Valens